ANALISIS YURIDIS PEMBATALAN MEREK “PENTAKOSTA” BERDASARKAN UNDANG-UNDANG MEREK DAN INDIKASI GEOGRAFIS: Juridical Analysis of the Cancellation of the 'PENTAKOSTA' Trademark Based on the Trademark and Geographical Indications Law - Refra, Mossad Kennedy; Purnamasari, Dian (AMICUS CURIAE, 2024)
"Pentecost" is a common term originating from the Bible centuries ago and marks a significant religious holiday for Christians, commemorating the day the Holy Spirit was bestowed upon Jesus' disciples in Jerusalem, occurring fifty days since the resurrection of Jesus Christ. While Christians celebrate the resurrection of Jesus Christ with Easter, Pastor J. Sihombing sought to register the term "Pentecost" as a trademark under class 45, a registration unknown to Pastor Ev. Diane Evapora Siburian and Pastor K. Siburian, leaders of the Pentecostal Church. The court decision resulted in the trademark "Pentecost" being revoked. This article discusses the legal aspects of registering "Pentecost" as a trademark. The research conducted is normative, descriptive, utilizing secondary data processed qualitatively to draw deductive conclusions. The conclusion drawn is that "Pentecost" cannot be registered as a trademark. It does not denote a product or service but rather references a Christian religious day and is part of a movement/branch within Christianity.